Results of Production-Condition Tests of the Aspiration System of the UXK Cotton Cleaning Unit (The Peerian Journal, 2025)
This article presents the results of comparative tests under production conditions of the current and improved aspiration systems of the UXK cotton cleaning unit in cotton processing enterprises.